Trend of cigarette smoking in Iranian adult population from 2000 to 2011 based on four national surveys - Meysamie, Alipasha; Ghalehtaki, Reza; Ghodsi, Saeed; Esteghamati, Alireza; Mohammad, Kazem; Etemad, Kouroush; Koohpayezadeh, Jalil; Shojaeefar, Ehsan (Social Determinants of Health, 2017)
Background: Tobacco smoking has been a major health concern for many years. People's awareness of the potential health hazards and government policies might change its pattern and prevalence of use. In order to monitor its conversion, determining the overall pattern of tobacco use and trend analyses would be crucial, which were aimed in the present study. Methods: Patterns of smoking in four national surveys conducted in years 2000, 2005, 2007, and 2011 with 33300, 89337, 5287, and 8837 participants, respectively, were assessed. Current status of cigarette, pipe and water-pipe smoking, the number of cigarettes used per day, and the age of smoking initiation were major parameters. After weighting based on province, residential area, gender, and age group, trend analysis was done through complex samples general linear model using IBM SPSS Statistics for Windows, Version 20.0. The values in the first survey (2000) were considered as reference points and categories. Results: While current cigarette smoking prevalence has been decreased (13.5% in 2000 to 11.3% in 2011) P<0.001, the average of pack-years increased. There was no significant decline in the mean age of initiation. It is also true for the prevalence of pipe and water-pipe smoking, which showed no noticeable difference compared to 2000. Conclusion: According to our findings it seems that health policy makers should focus more on designing programs targeting water-pipe consumption and also pay attention to the trends among subgroups for tailoring policies and scheme implementation.